Research hotspots and trends in the Historic Urban Landscape: a bibliometric perspective - Weihan Rong (Journal of Asian Architecture and Building Engineering)
As urbanisation accelerates and climate change intensifies, the tension between urban development the preservation of cultural heritage more pronounced. By adopting interdisciplinary integrative approach, the Historic Urban Landscape (HUL) offers a significant framework for amalgamating cultural heritage conservation and urban planning. This study employs a combination of bibliometric and qualitative analyses to evaluate the current status in the field as well as developmental trends. Furthermore, it utilises software tools to thoroughly analyse the development trajectory and evolution, identifying the most influential countries, institutions, and authors, a network and co-occurrence analysis of the HUL. Over the last 20 years, literature on the subject has increased significantly while research focuses have changed, moving from static preservation to adaptive reuse, cultural tourism, and technology integration. Europe and North America have been at the forefront of theoretical and technological advancement, whilst Asia and Latin America have added value through practical case studies. Nevertheless, social equity, ecological sustainability, and conservation practices in resource-limited environments remain significant gaps within the current literature. By constructing a knowledge map of the HUL, this study reveals the core issues and research hotspots and proposes future research directions, providing scientific basis for cultural heritage preservation and sustainable urban development.